2021
DOI: 10.3390/antiox10040566
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin K in Humans: Implication in Aging and Age-Associated Diseases

Abstract: As human life expectancy is rising, the incidence of age-associated diseases will also increase. Scientific evidence has revealed that healthy diets, including good fats, vitamins, minerals, or polyphenolics, could have antioxidant and anti-inflammatory activities, with antiaging effects. Recent studies demonstrated that vitamin K is a vital cofactor in activating several proteins, which act against age-related syndromes. Thus, vitamin K can carboxylate osteocalcin (a protein capable of transporting and fixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 231 publications
1
76
0
3
Order By: Relevance
“…MKs are cofactors used in the electron transport system (ETS) of bacteria to generate cellular energy, such as in the pathogenic Mycobacterium tuberculosis . [ 1 , 2 , 3 ] MKs consist of a naphthoquinone headgroup and an isoprenoid side chain of varying length ( Figure 1 ) [ 4 , 5 ]. We have previously found that MK’s structure allows it to fold into different molecular shapes depending on environment and side chain length [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…MKs are cofactors used in the electron transport system (ETS) of bacteria to generate cellular energy, such as in the pathogenic Mycobacterium tuberculosis . [ 1 , 2 , 3 ] MKs consist of a naphthoquinone headgroup and an isoprenoid side chain of varying length ( Figure 1 ) [ 4 , 5 ]. We have previously found that MK’s structure allows it to fold into different molecular shapes depending on environment and side chain length [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of vitamin K 1 supplementation is particularly evident in dialysis patients. In such patients, both a reduction of dp-ucMGP plasma levels and reduced arterial stiffness could be achieved [114][115][116][117][118] .…”
Section: Discussionmentioning
confidence: 99%
“…Third, OC shows a circadian rhythm with a night peak, and therefore, the time of blood sampling may also contribute to the variability of the obtained results [ 136 ]. Fourth, we are dealing with the influence of vitamin K [ 137 ] and vitamin D and the importance of supplementing these vitamins and bone metabolism status generally on the level of OC, which should also be taken into account. All these factors influence the interpretation of the results and should be reconsidered before OC becomes a recognized cardiovascular biomarker.…”
Section: Biomarkersmentioning
confidence: 99%